Haywire : poems - Bilgere, George, 1951- (May Swenson Poetry Award series., 2006)
This poet, you knew from his very first lines, didn't fall for anything phonyhis own language is irresistibly no-bullshit down to earth, even sassy ... Coming from one of the ethnic, industrial cities, his work has a gritty element. He recalls all the sorrows of a lifethe drunken father, the parents' divorce, his mother's death, his unremitting horniness, his own divorcenothing special, just what we all have to deal with one way or another.